(untitled) (VERUM: Journal of Scientific Initiation, 2024)
In this article, we seek to analyze how educational content, especially Geography and History books, together with narratives conveyed by the media, schools, and other institutions, perpetuate stereotypes and marginalize certain social groups. These practices contribute to the construction of a stigmatized and limited image of black people in various experiences and social practices. In addition, we explore how ideology is perpetuated by these media devices and how this is reflected in Education. We conclude that it is necessary to promote an education that favors social justice and equity, highlighting the importance of analyzing other educational materials and implementing policies that promote representation and inclusion in pedagogical practices.